Formulation Design and Development of Anti-EGFR-BSA-CYP-SLNs In Situ Gel for Nasal Administration - Bhattacharya, Sankha (Asian Journal of Pharmaceutics (AJP), 2016)
Aim: A comprehensive approach was taken in the modern era to develop new distinguished in situ gels, as it has good desirability, sustainability, self-administrative approach and bypassing first pass metabolism. In this context, we developed and designed nasal administrable in situ gel containing anti-epidermal growth factor receptor-body surface area-CYP-solid lipid nanoparticle for glioma treatment. Materials and Methods: After multiple screenings, gellan gum (0.25-0.75%), carbopol 934 (0.20-0.60%), and poloxamer 188 (0.20-0.40%) was taken as developing polymers. Box-Behnken design was used for formulation designing. Almost all the formulation (F1-F17) shown good results. Result and Discussion: The various evaluation parameters for all the formulations such as, viscosity (231 ± 1.22 to 656 ± 1.11 CPs), gelling strength (85 ± 0.9 to 180 ± 0.6 s), pH (5.7 ± 0.06 to 6.2 ± 0.08), gelling temperature (31.34 ± 0.78 to 37.34 ± 0.45°C), gel melting temperature (51.06 ± 0.23 to 55.23 ± 0.65°C), % drug content (94.12 ± 0.4 to 98.87 ± 0.1), spreadability (7.28 ± 0.23 to 10.84 ± 0.45 cm), and mucoadhesive strength (4619.56 ± 0.56 to 6501.86 ± 0.22 dyne/cm2) was been recorded. However, F8 turns out to be an optimized formula as it possess good dissolution profile (86.89% at 12th h), zero order kinetics (R2 = 0.9971), maximum desirability factor (D = 0.9921), minimum permeation (9.23% CDP after 720 min study), and maximum skin deposition (91.76%). Further F8 formulation was undergone for stability studies as per ICH Q1A (R2) guideline for 30 days. Conclusion: The results were satisfactory and signify good stability for F8 after 30 days of formulation development. However, further correlative in vivo studies were warranted for more conclusive outcome.